2020
DOI: 10.3390/f11010089
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Cold Acclimation-Regulated Protein Expression Profiles of Scots Pine Seedlings Reveal Potential for Adaptive Capacity of Geographically Distant Populations

Abstract: Geographically distant Scots pine (Pinus sylvestris L.) populations are adapted to specific photoperiods and temperature gradients, and markedly vary in the timing of growth patterns and adaptive traits. To understand the variability of adaptive capacity within species, molecular mechanisms that govern the physiological aspects of phenotypic plasticity should be addressed. Protein expression analysis is capable of depicting molecular events closely linked to phenotype formation. Therefore, in this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…According to Baniulis et al (2020) the comparative analysis of the protein content in the needles of pine seedlings provide insights into adaptation processes at the cellular level and the adaptive capacity within plant species.…”
Section: Discussionmentioning
confidence: 99%
“…According to Baniulis et al (2020) the comparative analysis of the protein content in the needles of pine seedlings provide insights into adaptation processes at the cellular level and the adaptive capacity within plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The green cluster mainly focused on photosynthesis and respiration acclimation of plants under different growth temperatures (especially high temperatures) associated with climate change [69,70,[76][77][78][79][80][81]. The yellow cluster mainly focused on the relationship between photoperiod and plant growth under temperature acclimation [82][83][84][85]. All three clusters have been the main research directions from 1986 to 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies have used genetic variation-based approaches to study stress memory and cross-tolerance, and to define stress resistance markers. Baniulis et al. (2020) identified constitutive differences in protein abundance associated with cold acclimation capacity in different P. sylvestris populations.…”
Section: Proteomics Survey (2012-2022): Where Are We Now?mentioning
confidence: 97%
“…Most recent studies have used genetic variation-based approaches to study stress memory and cross-tolerance, and to define stress resistance markers. Baniulis et al (2020) identified constitutive differences in protein abundance associated with cold acclimation capacity in different P. sylvestris populations. Garcıá-Campa et al (2022) identified proteins related to photorespiration, redox homeostasis, and secondary metabolism associated with transgenerational stress cross-tolerance and priming analyzing the chloroplast proteome of the progeny of two P. radiata populations with the same genetic background but from environmentally contrasting locations.…”
Section: Pinus Sppmentioning
confidence: 97%